2013
DOI: 10.1002/macp.201300470
|View full text |Cite
|
Sign up to set email alerts
|

A New Insight into the Mechanism of 1,3‐Dienes Cationic Polymerization I: Polymerization of 1,3‐Pentadiene with tBuCl/TiCl4 Initiating System: Kinetic and Mechanistic Study

Abstract: The cationic polymerization of 1,3-pentadiene using a tert -butyl chloride ( t BuCl)/TiCl 4 initiating system in CH 2 Cl 2 at different reaction conditions is reported. It is shown that the reaction rate increases with the increase of the t BuCl/TiCl 4 molar ratio, while the molecular weight distribution becomes narrower. Well-defi ned oligo(1,3-pentadiene)s (M n ≤ 3500 g mol − 1 ; M w /M n ≤ 3.0) are obtained at high t BuCl/TiCl 4 molar ratio (340) and low temperature (-78 °C). 1 H and 13 C NMR spectroscopy s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 49 publications
(165 reference statements)
6
32
0
Order By: Relevance
“…Based on these data we can conclude that six‐membered cyclic structures are absent in a polymer chain of cationic polyisoprene. This observation is fully consistent with the earlier reported absence of six‐membered cyclic structures in a polymer chain of cationic poly(1,3‐pentadiene) . Based on the above‐mentioned results we can unambiguously conclude that reduced unsaturation of polyisoprene synthesized via cationic mechanism is not a result of intramolecular cyclization and other processes are responsible for the decrease of unsaturation of a polymer chain.…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Based on these data we can conclude that six‐membered cyclic structures are absent in a polymer chain of cationic polyisoprene. This observation is fully consistent with the earlier reported absence of six‐membered cyclic structures in a polymer chain of cationic poly(1,3‐pentadiene) . Based on the above‐mentioned results we can unambiguously conclude that reduced unsaturation of polyisoprene synthesized via cationic mechanism is not a result of intramolecular cyclization and other processes are responsible for the decrease of unsaturation of a polymer chain.…”
Section: Resultssupporting
confidence: 92%
“…The formation of branched structures occurs through “grafting onto” mechanism via interaction of growing macrocations with double bond of the polymer chain with creation of branched point. The “grafting from” mechanism, which is consistent with the chain growth from branched macrocations as macroinitiators, can also operate under these conditions . The formation of branched polyisoprene during cationic polymerization of isoprene was confirmed in our earlier work .…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…It should be noted that above‐mentioned signals of carbon atoms belong only to unsaturated part of polymer chain. According to the following works, the spectral signals belonging to carbon atoms at the branching points of polyisoprene chain are located under the pedestal line of 13 C NMR spectrum, and, therefore, were not characterized by NMR spectroscopy up to date. Besides, it was recently shown that six‐membered cyclic structures are totally absent in polyisoprene obtained by cationic polymerization of isoprene with t BuCl/TiCl 4 initiating system .…”
Section: Resultsmentioning
confidence: 99%